COMPARISON OF ERROR METRICS IN MATCHING ALGORITHMS OF IMAGES BY SURF DETECTOR - Mukhina, Maryna (Proceedings of National Aviation University (archive), 2014)
Speed-Up Robust Feature (SURF) method is used to detect feature points of images. The analyses ofmatching algorithms of feature points is done. The comparison of different error metrics by their accuracy andcomputing efficiency is provided on the series of test images for basic transforms like scaling, rotation and shifting.